Pengaruh Sikap Generasi Z Terhadap Minat Menjadi Nasabah Bank Syariah dengan Literasi Keuangan Syariah Sebagai Variabel Moderasi (Studi Kasus Mahasiswa Kota Payakumbuh Tahun 2024) - Niken Fitmayuri; Finantyo Eddy Wibowo; Ahmad Nuh (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Sharia banking in the financial services sector is an intermediary institution for people who follow Islamic principles which consider bank interest to be haram. The growth of the sharia banking sector requires an understanding of the factors that influence the interest of the younger generation in becoming sharia bank customers. This research aims to analyze the influence of Generation Z attitudes on their interest in becoming Islamic bank customers with Islamic financial literacy as a moderating variable. This study focuses on generation Z in Payakumbuh City in 2024. The research method used was a survey with a quantitative approach, involving Generation Z samples spread across the area. Data was collected through a questionnaire designed to measure attitudes towards Islamic banks, level of Islamic financial literacy, and interest in becoming a customer. Data analysis was carried out using simple regression techniques with moderation to assess the influence of Generation Z attitudes on their interests, as well as the moderating role of Islamic financial literacy. The research results show that a positive attitude towards sharia banks has a significant effect on generation Z's interest in becoming sharia bank customers. Attitudes moderated by sharia financial literacy have no effect on interest in becoming a sharia bank customer. These findings provide important insights for Islamic banks in designing effective marketing and education strategies to attract customers from generation Z.